Review of Diagnostic Procedures and Approaches to Infectious Causes of Reproductive Failures of Cattle in Australia and New Zealand - Reichel, Michael P.; Wahl, Lloyd C.; Hill, Fraser I. (Frontiers in Veterinary Science, 2018)
Infectious causes of reproductive failure in cattle are important in Australia and New Zealand, where strict biosecurity protocols are in place to prevent the introduction and spread of new diseases. Neospora caninum ranks highly as an important cause of reproductive wastage along with fungal and bacterial infections. Brucella, a leading cause of abortion elsewhere in the world, is foreign, following successful programs to control and eradicate the disease. Leptospirosis in cattle is largely controlled by vaccination, while Campylobacter and Tritrichomonas infections occur at low rates. In both countries, Bovine Viral Diarrhea virus (BVDV) infection rates as the second most economically important disease of cattle and one that also has an effect on reproduction. Effective disease control strategies require rapid diagnoses at diagnostic laboratories. To facilitate this process, this review will discuss the infectious causes of reproductive losses present in both countries, their clinical presentation and an effective pathway to a diagnosis.